Las relaciones públicas en los procesos de posicionamiento de la empresa multicomercio la floresta de la ciudad de Riobamba. periodo 2017 - Carrillo Atupaña, Sandy Mariela (2018)
This research work entitled "Public relations in the process of positioning of the company La Floresta multicommercial period 2017" dedicated to market furniture home, office, among others. Its main objective is to determine what the effects of Public Relations are in the positioning processes of the Multicomercio La Floresta company in the city of Riobamba, Period 2017. It consists of four different chapters: In the first part we will find the introduction of the investigative work, followed by the problem statement which describes the problems that exist in the company La Floresta multicommercial since this information helped us to plate the general objective and the specific objectives that are indicated in this section. In the second part we can find the state of art that is formed by the background of research similar to ours. It consists of three units, the first will find information on public relations, the second on positioning and the third on the company La Floresta multicommercial. In the third part, the methodology of the research that was used is established, we also find the population and show that it was taken to gather the necessary information, and then proceed with the analysis of the tabulation of results. In the last part we present the conclusions and recommendations about the research work and finally we have the bibliographical references used and the annexes.